An Evaluation of Evidence Underpinning Management Recommendations in Tobacco Use Disorder Clinical Practice Guidelines. Issue 6 (12th February 2022) - Streck, Sam; McIntire, Ryan; Canale, Lawrence; Michael Anderson, J; Hartwell, Micah; Torgerson, Trevor; Dunn, Kelly; Vassar, Matt
Abstract: Introduction: Clinical practice guidelines(CPGs) are important tools for medical decision-making. Given the high prevalence and financial burden associated with tobacco use disorder(TUD), it is critical that recommendations within CPGs are based on robust evidence. Systematic reviews(SRs) are considered the highest level of evidence, thus, we evaluated the quality of SRs underpinning CPG recommendations for TUD. Methods: We used PubMed to search for CPGs relating to TUD published between January 1, 2010 and May 21, 2021. SRs were extracted from CPG references and evaluated using Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA) and A MeaSurement Tool to Assess Systematic Reviews(AMSTAR-2) tools. We then compared SRs conducted by the Cochrane Collaboration with non-Cochrane SRs using a Mann-Whitney U test and determined associations between PRISMA and AMSTAR-2 extracted characteristics using multiple regression. Results: Our search generated 10 CPGs with 98 SRs extracted. Mean PRISMA completion was 74.7%(SD = 16.7) and mean AMSTAR-2 completion was 53.8%(SD = 22.0) across all guidelines. Cochrane SRs were more complete than non-Cochrane studies in the PRISMA and AMSTAR-2 assessments. The regression model showed a statistically significant association between PRISMA completion and AMSTAR-2 rating, with those classified as "low" or "moderate" quality having higher PRISMA completion than those with "critically low" ratings. Conclusion: We found substandard adherence to PRISMA and AMSTAR-2 checklists across SRs cited in TUD CPGs. A lack of recent SRs in CPGs could lead to outdated recommendations. Therefore, frequent guideline updates with recently published evidence may ensure more accurate clinical recommendations and improve patient care. Implications: Systematic reviews used to underpin clinical practice guideline recommendations influence treatment decisions and, ultimately, patient outcomes. We found that many systematic reviews underpinning tobacco use disorder guideline recommendations were out of date and unsatisfactory in reporting and quality. Thus, including newer systematic reviews containing more recently conducted trials and better reporting could alter recommendations and improve the rate of successful tobacco cessation attempts.